M. tuberculosis Hypothetical Proteins and Proteins of Unknown Function: Hope for Exploring Novel Resistance Mechanisms as well as Future Target of Drug Resistance - Sharma, Divakar; Bisht, Deepa (Frontiers in Microbiology, 2017)
Drug resistance in tuberculosis predominantly, mono-resistance, multi drug resistance, extensively drug resistance and totally drug resistance have emerged as a major problem in the chemotherapy of tuberculosis. Failures of first and second line anti-tuberculosis drugs treatment leads to emergence of resistant M.tuberculosis. Few genes are reported as the principal targets of the resistance and apart from the primary targets many explanations have been proposed for drug resistance but still some resistance mechanisms are unknown. As proteins involved in most of the biological processes, these are potentially explored the unknown mechanism of drug resistance and attractive targets for diagnostics/future therapeutics against drug resistance. In last decade a panel of studies on expression proteomics of drug resistant M.tuberculosis isolates reported the differential expression of uncharacterized proteins and suggested these might be involved in resistance. Here we emphasize that detailed bioinformatics analysis (like molecular docking, pupylation and proteins-proteins interaction) of these uncharacterized and hypothetical proteins might predict their interactive partners (other proteins) which are involved in various pathways of M.tuberculosis system biology and might give a clue for novel mechanism of drug resistance or future drug targets. In future these uncharacterized targets might be open the new resistance mechanism and used as potential drug targets against drug resistant tuberculosis.